Tests on verbal Aktionsart applied to Ancient Egyptian - Gracia Zamacona, Carlos (AAeO - Afrikanistik-Aegyptologie-Online, 2015)
A cluster of 37 tests largely employed to determine verbal Aktionsart is described, in order to provide a corpus-based approach with instruments of analysis. These tests are illustrated with 56 examples of several Ancient Egyptian verbs, different in Aktionsart, which occur in an extensive textual corpus, the Coffin Texts, dating back to circa 2000-1500 BCE. A systematic application of these tests upon the verb prj ‘go out, go up’, one of the most frequent in that corpus, is also proposed in order to display the relevant results of this analysis (22 examples are adduced for this verb). Finally, equivalence between the Egyptological transliteration and the IPA encoding, as well as a collection of the main literature relevant to these tests, are given in two appendices.